2013
DOI: 10.1177/0263276413500828
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Techniques: Preliminary Remarks

Abstract: These introductory remarks outline the German concept of Kulturtechniken (cultural techniques) by tracing its various overlapping meanings from the late 19th century to today and linking it to developments in recent German theory. Originally related to the agricultural domain, the notion of cultural techniques was later employed to describe the interactions between humans and media, and, most recently, to account for basic operations and differentiations that give rise to an array of conceptual and ontological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(28 citation statements)
references
References 10 publications
(9 reference statements)
0
27
0
1
Order By: Relevance
“…Now cultural techniques as a notion has different meanings connected to different historical periods (see Siegert, 2013;Winthrop-Young, 2013) Winthrop-Young exemplifies this statement by noting that people draw pictures before the concept of an image was conceived and played music before the concept of tonality existed. Concepts do not have ontological priority, rather they emerge from practice (Winthrop-Young, 2015, p.459).…”
Section: Cultural Techniques or Ethics As Method Methods As Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now cultural techniques as a notion has different meanings connected to different historical periods (see Siegert, 2013;Winthrop-Young, 2013) Winthrop-Young exemplifies this statement by noting that people draw pictures before the concept of an image was conceived and played music before the concept of tonality existed. Concepts do not have ontological priority, rather they emerge from practice (Winthrop-Young, 2015, p.459).…”
Section: Cultural Techniques or Ethics As Method Methods As Ethicsmentioning
confidence: 99%
“…Geoffrey Winthrop-Young (2013) proposes that "Rather than tackling the question 'What are cultural techniques? ', it makes more sense to ask: 'What is the question to which the concept of cultural techniques claims to be an answer?'"…”
Section: Location and Datamentioning
confidence: 99%
“…The speaker suggested the notion of cultural techniques (Siegert 2013, Winthrop-Young 2013 for bringing together discussions on materiality, practices as well as signs and text into the historical analysis of software. Using the example of business games, he suggested that practices often preclude discourse.…”
Section: Book Reviewsmentioning
confidence: 99%
“…Originally it was used in the agricultural domain, where it refers to "cultivation of land". More recently it has gained a layered set of meanings (Winthrop-Young, 2013). Since the 1970s the term has been used in media theoretical contexts, where the distinction between culture and nature has been a key point of reference for discussions on the societal impact of technology.…”
Section: Cultural Techniquesmentioning
confidence: 99%